2011
DOI: 10.4236/epe.2011.34063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Gas Turbine Inlet Temperature with Relation to the Excess Air

Abstract: This paper shows the effect of excess air on combustion gas temperature at turbine inlet, and how it determines power and thermal efficiency of a gas turbine at different pressure ratios and excess air. In such a way an analytic Equation that allows calculating the turbine inlet temperature as a function of excess air, pressure ratio and relative humidity is given. Humidity Impact on excess air calculation is also analyzed and presented. Likewise it is demonstrated that dry air calculations determine a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 5 publications
(8 reference statements)
0
10
0
3
Order By: Relevance
“…In practise, this is achieved by increasing excess air ratio [16]. Compression of the excess air is energy consuming, therefore the assumption that the low calorific syngas combustion could reduce this energy penalty, since its combustion proceeds at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In practise, this is achieved by increasing excess air ratio [16]. Compression of the excess air is energy consuming, therefore the assumption that the low calorific syngas combustion could reduce this energy penalty, since its combustion proceeds at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the excess air is also utilized to protect the turbine components from being overheated. Martínez et al reported that 600% to 100% excess air is required to maintain the turbine inlet temperature in the range of 800-1700°C while a methodology is presented to determine the turbine inlet temperature using the excess air and the pressure ratio [41]. In the present work, the excess air in the actual combustion process for different electrical loads is calculated from the actual fuel to air ratio.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 98%
“…Sabendo que um fluido ao sofrer processo de expansão ou compressão que seja reversível e adiabático, então este processo é isentrópico (Smith et al, 2000). A eficiência de um compressor isentrópico é calculada pela equação 1 a seguir:…”
Section: Modelagem Do Compressorunclassified
“…De acordo com o trabalho publicado por Martínez et al (2011), a maior temperatura de operação de turbinas comumente usadas na indústria é de 1700 °C, portanto, para manter a operação o modelo aqui apresentado em níveis aceitáveis, a temperatura do gás que entra na turbina será estipulada para 1500 °C.…”
Section: Ufscar -São Carlos -Sp 16 a 19 De Julho De 2017unclassified